Onze schouwburg : orgaan van "De Vrienden van den Koninklijken Nederlandschen Schouwburg van Gent". (Gent : VKNS, 1934)
Bibliotheek E. Anseele
Periodiciteit: maandelijks
Nederlands
Krant
Keywords: toneel